STRATEGI PENGELOLAAN HUTAN RAKYAT PINANG JAYA KEMILING DENGAN ANALISIS SWOT - siti herawati sitorus; Rahmat Safe’i; Susni Herwanti (Tengkawang : Jurnal Ilmu Kehutanan, 2021)
Community forest has a very important role in influencing environmental sustainability. Good management at community forest will affect the welfare of the community around the forest. This study aims to determine the strategy of community forest management in Pinang Jaya Kemiling Bandar Lampung. The data were collected with observation, documentation study and deeply interview with community forest farmers. The method of analysis used in this research is descriptive qualitative. The strategy for managing the community forest in Pinang Jaya analyzed with SWOT analysis (Strengths, Weaknesses, Opportunities and Threat). Based on the research, the results of the identification of internal factors, there are two strengths and four weaknesses, Meanwhile, for external factors, there are five opportunities and one threat. The SWOT diagram shows that the position of the Pinang Jaya community forest management strategy lies in quadrant three or diversification strategy by using the power possessed and avoid any available threats. Keywords : Community forest, management at community forest, SWOTAbstrakHutan rakyat memiliki peran yang sangat penting dalam mempengaruhi kelestarian lingkungan. Pengelolaan hutan rakyat yang baik akan berdampak pada kesejahteraan masyarakat sekitar hutan. Penelitian ini bertujuan untuk mengetahui strategi pengelolaan hutan rakyat di Pinang Jaya Kemiling Bandar Lampung. Pengumpulan data dilakukan dengan observasi, studi dokumentasi dan wawancara mendalam dengan petani hutan rakyat. Metode analisis yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Strategi pengelolaan hutan rakyat di Pinang Jaya dianalisis dengan analisis SWOT (Strengths, Weaknesses, Opportunities and Threat). Berdasarkan penelitian diperoleh hasil identifikasi faktor internal terdapat dua kekuatan dan empat kelemahan, sedangkan untuk faktor eksternal terdapat lima peluang dan satu ancaman. Diagram SWOT menunjukkan bahwa posisi strategi pengelolaan hutan rakyat Pinang Jaya berada pada kuadran tiga atau strategi diversifikasi dengan menggunakan kekuatan yang dimiliki dan menghindari ancaman yang ada.Kata Kunci: Hutan rakyat, Pengelolaan Hutan rakyat, SWOT